The emotional path to influencing decision-making: harnessing emotions for better financial choices - Born, Nadja; Ashebir, Sophia; Brady, Samantha; D'Ambrosio, Lisa; Coughlin, Joseph (Frontiers in Behavioral Economics, 2024)
Introduction As life expectancy and expected years in retirement rise and family structures change, the need for personal financial protections, such as long term care (LTC) insurance, in managing financial risks associated with later life is expected to increase. Roughly half of American households are at risk of not being able to maintain their present standards of living post-retirement. Because both public and private health insurance programs typically do not cover LTC needs, which are associated with significant costs, the potential demand for LTC further exacerbates the retirement savings crisis. Methods Using an original survey experiment, in this high-powered study (N = 1,450), we examine the impact of a 2×3 framing intervention on participants' attitudes, emotions, and behavioral intentions toward LTC insurance. Results Results indicated that direct framing effects were present for people's reported emotions: those who received a loss frame (compared to a gain frame) were more likely to report anxiety-related emotions, and those who were exposed to a care choice narrative frame (compared to a family or a financial frame) were more likely to report calmness-related emotions. There were no significant interaction effects between loss/gain and narrative frames. A mediation analysis suggested that the framing impacts acted through these two different emotional pathways to yield more positive attitudes toward and behavioral intentions around LTC. Implications The study results underscore the need to examine how different frames affect emotional arousal as a potential pathway to impacting attitudes and behaviors. We found that both a loss framing and a narrative framing, operating through different emotional pathways, have the potential to be helpful to nudge people to hedge against a financial risk associated with older age.